Alghero, il disegno delle trasformazioni - Bagnolo, Vincenzo; Pirinu, Andrea (Scienze del Territorio, 2017)
Drawing may be interpreted as the tool that allows us to recognize, break down and sort the different parts of a phenomenon, translating them into signs, expressing the sense of reality, revealing and transposing in the graphic expression the different meanings you want to state. Distinguishing between the perceived data and the ones derived from interpretation, there is no one single truth, but a plurality of worlds with several parallel representations all equally valid. The perception returns ‘images’ of reality, and the drawing turns on new levels of meaning: everything can be reduced to an image, but graphing only evokes some aspects of physical reality. The path of knowledge can seek a vision of objective, empirical reality, or a symbolic image leading to the recognition of the urban structure as a concept connected to a reference model. In the graphic investigation of the form of Alghero, different approaches have been taken. A first assumption has been that the representation of the city can be understood as a translation of the life space of a community. A second approach has assumed drawing as a tool to emphasize the urban invariants noticeable within a fixed period of time, in order to return a transformations pattern in a historical and morphological context. The third criterion, finally, has been aimed at identifying an ‘ideal form’ representing the ‘archetype’ of the city.